2012
DOI: 10.1021/jf3028842
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Inflammatory Gene Expression by a Bilberry (Vaccinium myrtillus L.) Extract and Single Anthocyanins Considering Their Limited Stability under Cell Culture Conditions

Abstract: Studies with nonintestinal models indicate that anthocyanin-rich extracts can modulate inflammatory gene expression and may help prevent development of inflammatory bowel diseases (IBD). This work investigated the influence of a bilberry ( Vaccinium myrtillus L.) extract (BE) and comprising anthocyanins on pro-inflammatory genes in IFN-γ/IL-1β/TNF-α stimulated human colon epithelial cells (T84) by qRT-PCR and cytokine arrays. Moreover, the stability of selected anthocyanins under cell culture conditions was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 34 publications
3
38
1
2
Order By: Relevance
“…We demonstrated that not only STAT1 and STAT3 phosphorylation was inhibited by BE but also target gene expression (IL-6, MCP-1, ICAM-1, and T-bet) and cytokine secretion (MCP-1 and TNF-α). Our data correlate with Triebel et al [10] who evaluated effects of BE in human colon epithelial cells T84. In our experiments, we confirmed that BE prevents IFN-γ-induced pro-inflammatory signalling in THP-1 mononuclear cells and T84 IEC.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We demonstrated that not only STAT1 and STAT3 phosphorylation was inhibited by BE but also target gene expression (IL-6, MCP-1, ICAM-1, and T-bet) and cytokine secretion (MCP-1 and TNF-α). Our data correlate with Triebel et al [10] who evaluated effects of BE in human colon epithelial cells T84. In our experiments, we confirmed that BE prevents IFN-γ-induced pro-inflammatory signalling in THP-1 mononuclear cells and T84 IEC.…”
Section: Discussionsupporting
confidence: 91%
“…Various studies provide evidence that anthocyanin extracts inhibit inflammatory gene expression in vitro [8,9,10]. Moreover, it has been demonstrated that anthocyanins from bilberries (also called blueberries) decrease pro-inflammatory cytokine serum levels and attenuate the severity of experimental colitis in mice [11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…These pro-inflammatory mediators are regulated by NF-kB during the pathogenesis of inflammation. Previous studies found that both anthocyanins-rich extracts and single anthocyanins can modulate gene expression of pro-inflammatory mediators in vitro and in vivo (Chao et al, 2010;Triebel et al, 2012;Yun et al, 2008). Furthermore, Karlsen et al (2007) discovered strong antiinflammatory effects of anthocyanins by their inhibition of NF-kB and pro-inflammatory chemokine expression in monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The ACN profile of the WB used in the current research differs from that of previous studies in both qualitative and quantitative composition. 28,29 Generally, Mv-, Dp-, Cy-, Pt-, and Pe-glycosides are the most abundant ACNs found in wild blueberry. 9,30,31 In the ACN-rich fraction prepared for this study that originated from wild blueberry (Vaccinium angustifolium), the dominant compounds were Mvglycosides (35% of the total ACN amount), Dp-glycosides (31%), and Cy-glycosides (19%).…”
Section: ■ Discussionmentioning
confidence: 99%